Probiotic characteristics and whole genome sequencing of Pediococcus pentosaceus SNF15 and its protective effect on mice diarrhea induced by Escherichia coli K99 - Su, Yalan; Feng, Mingque; Tong, Jingdi; Wen, Xiangfu; Ren, Meiyi; Song, Deyuan; Song, Jinshang; Li, Xiaohan; Xie, Qinna; Cheng, Jia; Liu, Mingchao (Frontiers in Veterinary Science, 2025)
Escherichia coli (E. col iK99) is one of the primary pathogens that cause infectious calf diarrhea, resulting in mortality and causing economic losses. Probiotics have been widely researched for their positive impact on inhibiting the growth of pathogenic bacteria and enhancing immunity and gut health as alternatives to antibiotics. This study isolated one probiotic from healthy calf feces: Pediococcus pentosaceus SNF15 (P. pentosaceus SNF15). In vitro assessments included growth character and acid-producing ability, bile salt and artificial gastroenteric fluid tolerance, Caco-2 adhesion, hemolysis screening, and antibiotic susceptibility. Whole-genome sequencing identified immunomodulatory, antimicrobial, and metabolic genes. A murine model evaluated probiotic efficacy against E. coli K99, outcomes included clinical indices (fecal score, weight), histopathology (H&E), inflammatarty factor (qRT-PCR and ELISA), tight junction proteins and mucin (immunohistochemistry detection). Finally, 16S rRNA sequencing was performed to compare the composition and relative abundance of the gut microbiota among the different groups. P. pentosaceus SNF15 demonstrated excellent growth performance and acid production capacity, bile salt and artificial gastroenteric fluid resistance, Caco-2 cells adhesion and safety (γ-hemolysis, antibiotic sensitivity) Genomic analysis revealed to immune, anti-inflammatory, antagonistic pathogens, and carbohydrate utilization, including secondary bile acid, nicotinate and nicotinamide. The animal tests showed that the P. pentosaceus SNF15 treatment protects against E. coli K99 infection, as evidenced by clinical symptoms, including weight loss, fecal score, liver atrophy, and spleen enlargement occurred histological damage. Compared with the CN group, the supplementation of P. pentosaceus SNF15 strains ameliorated the damage of jejunum and the content of tight junction proteins occludin, claudin, ZO-1, and MUC2 and decreased the levels of IL-6, IL-1β, and TNF-α in jejunum. The 16S rDNA sequence results showed that infection with Escherichia coli K99 led to an imbalance in gut microbiota; the proportion of Firmicutes and Bacteroidetes decreased, and Proteobacteria increased. P. pentosaceus SNF15 helps improve intestinal microbial composition and prevents this trend. P. pentosaceus SNF15 supplementation can prevent and treat the clinical symptoms, intestinal epithelial mucosal integrity, intestinal permeability, and immune-related cytokines and regulate the intestinal microbiota in E. coli K99-infected mice. This research revealed that P. pentosaceus SNF15 possesses desirable probiotic characteristics and could be used as a potential probiotic to remit neonatal calf diarrhea, caused by E. coli K99 infection.